Integração de mercados, sustentabilidade da dívida e pobreza: três ensaios de modelos para dados em painel - Tabosa, Francisco José Silva (2010)
The use of panel data in economic studies becomes increasingly constant, because it has more advantages than pure medium cross-section or pure time series. Thus obtain more efficient econometric estimates. Another important point arises from the possibility to isolate the effects of specific actions, treatments or policies in General. In this sense, this study seeks to examine three cases in the Brazilian economy using state data in the pane. In chapter I, to examine the existence of market integration Brazilian wholesaler, tomato using a dynamic Panel that allows effects thresholds (threshold) to test the hypothesis that the market convergence to the law of one price. The results support the hypothesis of integration between the main tomato and Brazilian markets in this process there is empirical evidence of transaction costs. In chapter II seeks to analyze the sustainability of the debt of Brazilian States after implementation of the law of fiscal responsibility (LRF) through fiscal response function of Government, this methodology developed by Bohn (2006). To this end, it was estimated econometric model for data on Panel with annual data for the period 2000-2008 for the stock of net debt and spending and revenue streams. The results show that the Brazilian States do not respond as expected to keep their debts sustainable. In chapter III, sought to analyse the effects of economic growth, inequality and the Bolsa Familia program (PBF) in poverty rates in Brazil. This was a model of dynamic Panel, estimated by the generalized method of moments for two-pass system, developed by Blundel-Bond (1998). The results show that spending on the bolsa família did not, in any of the models examined, impact on poverty. It was found that the average family income rises per capita as the reduction of inequality are statistically significant in combating poverty, whether in the proportion of poor or indigent ratio and that economic growth policies that promote increased income together with the reduction of their disparities are preferable to economic growth policies that favor simply increased incomes average in combating poverty in Brazil.